2020
DOI: 10.1029/2020jb020485
|View full text |Cite
|
Sign up to set email alerts
|

Shear Wave Splitting Evidence for Keel‐Deflected Mantle Flow at the Northern Margin of the Ordos Block and Its Implications for the Ongoing Modification of Craton Lithosphere

Abstract: We use 123 temporary seismic stations to determine shear wave splitting patterns beneath the northern Ordos block and its surrounding areas. The mapped pattern of anisotropy shows a dramatic arc-shaped anisotropy contrast beneath the northeastern Ordos block that closely follows the lateral fast/slow-velocity interface seen in a recent surface tomographic model at~140 km depth. Both seismic anisotropy and velocity appear to demarcate the current boundary of cratonic lithosphere in the upper mantle at this dept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 77 publications
(147 reference statements)
1
3
0
Order By: Relevance
“…Our results with higher resolution at shallow depths clearly illustrates that the cold and seismically fast cratonic keel at the southeastern margin of Ordos block has been replaced by asthenosphere at 60-200 km depths, where an anti-clockwise flow occurs (Yu & Chen, 2016). A similar lithosphere reworking has been reported at the northeastern corner of Ordos (Li et al, 2020), forming a lithospheric divot that influence the mantle flow direction. Thus, we suggest that the lithospheric reworking around the Ordos block is likely to be an ongoing process that is caused by thermal-chemical erosion induced by mantle flow around the Ordos (Figure 10).…”
Section: Asthenosphere-lithosphere Interaction and Continental Deform...supporting
confidence: 76%
“…Our results with higher resolution at shallow depths clearly illustrates that the cold and seismically fast cratonic keel at the southeastern margin of Ordos block has been replaced by asthenosphere at 60-200 km depths, where an anti-clockwise flow occurs (Yu & Chen, 2016). A similar lithosphere reworking has been reported at the northeastern corner of Ordos (Li et al, 2020), forming a lithospheric divot that influence the mantle flow direction. Thus, we suggest that the lithospheric reworking around the Ordos block is likely to be an ongoing process that is caused by thermal-chemical erosion induced by mantle flow around the Ordos (Figure 10).…”
Section: Asthenosphere-lithosphere Interaction and Continental Deform...supporting
confidence: 76%
“…This mantle flow model can also be used to interpret splitting measurements conducted to the north of our study area (Lu et al, 2020), where a southeastward opening U-shaped pattern in the fast direction, or a rotation pattern, has been revealed, and the authors explained it with complicated flows in both horizontal and vertical direction in the BMW. Although the keel-deflected mantle flow has been reported in other regions, for example, Eastern US and Northeastern Ordos (Li et al, 2020;West et al, 2009;Yang et al, 2017), this is the first time to show it clearly across the NSGL, and we infer that the location of the deflected keel might mark the frontier of the Pacific subduction regime (Figure 4b).…”
Section: Distinct Anisotropy Variation: Keel-deflected Mantle Flow Ac...mentioning
confidence: 46%
“…Furthermore, seafloor spreading in the Mariana Trough, which started from the Miocene and has continued to the present day (Seton et al., 2020), creates space beneath the Philippine Sea Plate to draw in asthenospheric materials from NE Asia (see Figure 1a). It has long been suggested that the slab roll‐back of the Pacific Plate and far‐field effects of the Indian‐Eurasian continental collision induces widespread eastward mantle flow beneath the eastern China, although the destination of the mantle flow is controversial (Jolivet et al., 2018; S. Li et al., 2020; Schellart et al., 2019; Yu & Chen, 2016). Our study suggests that at least part of the eastward asthenospheric materials from East China do flow into the Philippine Sea Plate through the slab window beneath the Nankai Trough.…”
Section: Discussionmentioning
confidence: 99%